Nīlayakshiṇī - Satyarthi, Devendra (Parāga Prakāśana, 1985)
Short stories, autobiographical pieces, poems, reminiscences about Indic authors, etc., by a Hindi writer and folklorist; includes short pieces on him by his contemporaries.